The Effect of Idiom Instruction on EFL Teenage Learners’ Retention of Idioms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The present study investigated the effect of idiom instruction on EFL teenage learners’ retention of idiom knowledge. The focused techniques used in the intervention were contextual clues, L1-L2 idiom comparison and pictures. Thirty common English idioms were introduced to 37 pre-intermediate Vietnamese students in a private language center in the Mekong delta. During the experiment, idiom tests, IKT and VKSIT, were employed to gauge the effect of instruction on the learners’ knowledge. The intervention was controlled carefully for each single technique so that the effects of each technique could be seen clearly. Along with classroom observations for tracking objectives and procedures of instruction, face-to-face interviews were employed for gaining the insights into the learners’ attitudes towards learning idioms. The findings showed that all of the participants’ posttest results in both IKT and VKSIT were much higher than their pretest results. These results suggested the positive effect of idiom instruction on learners’ retention. Moreover, the interviews showed that the use of pictures was the most preferred learning technique of the three. These findings added pedagogical values of these techniques in teaching idioms. Suggestions were made to enhance learner attitudes towards idiom learning..